The Use of Vasoconstrictors in Acute Variceal Bleeding: How Long Is Enough? - Gin-Ho Lo (Korean Society of Gastrointestinal Endoscopy, 2019)
Vasoconstrictors are often used as the first line therapy for acute esophageal variceal hemorrhage. They might also be used for a few days after endoscopic therapy to prevent early rebleeding. International guidelines recommend the use of vasoconstrictor therapy when acute esophageal variceal hemorrhage is suspected and continuation of the therapy until 3 to 5 days after endoscopic treatment. However, the duration of use of vasoconstrictors after endoscopic therapy is not clear. This review shows that if variceal bleeding is successfully controlled by endoscopic variceal ligation, the combination of vasoconstrictors can be reduced to less than 1 day.